CRITICAL GEO-POLITICS AND ROLE OF IDENTITY - Naresh Kumar Bhari (Galaxy International Interdisciplinary Research Journal, 2021)
Notion of Geopolitics has its historical path in a close interaction with International politics.Different phases denote the primacy of ideas of the time. This paper seeks to analyse this development of geopolitical thought with special emphasis to the significance of narrative,identity and discourse in critical geopolitics. Critical geopolitics contrary to classical theories do not offer objective and final truth but advocates a perspective consist of some ontologicalepistemological-methodology-axiology questions. This perspective is very crucial to understand the choices adopted by the nation states.